Public service radio in Poland vs technology challenges: A turning point. (1st April 2018) - Jędrzejewski, Stanislaw; Beliczyński, Jan
This article deals with the technology challenges that public service radio is currently facing in Poland and with its response to those. The challenges have occurred in the context of the remit of radio public broadcaster. The context is quite complex and is made up of a number of elements connected with both a new concept of a public broadcaster and changes within the broadcasting organization itself, and the way in which the technology change is managed.